PERLINDUNGAN HUKUM BAGI PEMILIK MEREK DAGANG TERHADAP PELANGGARAN HAK MEREK DALAM PERDAGANGAN DIGITAL DITINJAU DARI PERSPEKTIF SISTEM HUKUM - Asyisyifa, Ananda Fia; Gultom, Elfrida; Rahmawan, Dhany; Indirahati, Novina Sri; Bustani, Simona (Ensiklopedia of Journal, 2025)
Abstract: Since the free trade era began, brand protection has become increasingly important because some brands are now widely known and can even reach all corners of the world. However, due to the rapid development of technology, many business actors sell fake or counterfeit goods through digital trade or e-commerce, causing the original owner of the trademark to experience losses. This article discusses legal protection for trademark owners against trademark rights violations in digital commerce from a legal system perspective, where the conclusion of this article is that Indonesia is a country that adheres to a civil law system legal culture as also adopted by continental European countries. which prioritizes positive law or written law, is obliged to provide legal certainty regarding legal protection for trademark owners for violations of trademark rights in digital commerce.Keywords: E-commerce, Merk.